some aspects of four-year-plus old stage in the acquisition of Tamil phonology - Thirumalai MS (Journal of All India Institute of Speech and Hearing, 1972)
The completion of age four for a child is a very crucial stage in its acquisition oflanguage. It is generally agreed that a large amount of syntax is now known to thechild and that though the linguistic development continues long after, this developmentinvolves mainly such matters as style and possibly semantics but not apparentlysyntax (Slobin, 1966 & 1971). In other words, having completed successfully theacquisition of the rudiments of a language, the child is now assumed to be involved inprocesses of acquisition which would enable him to produce utterances matchingadult speech.